A regenerated O3 type high entropy layered sodium ion battery positive electrode material and preparation method thereof
A regenerated O3-type high-entropy layered sodium-ion battery cathode material addresses inefficiencies in lithium-ion recycling by using a mixed salt solution to create a high-performance sodium-ion battery cathode, enhancing electrochemical and thermal stability, and enabling the recycling of waste lithium batteries, with a specific chemical formula Na1-aLi a Ni x Fe y Mn z Co m Al n O2, where Na and Li are in the alkali metal layer and Ni, Fe, Mn, Co, Al, and Cu are in the transition metal layer, arranged disorderly, and a specific preparation method involving sulfate leaching, precipitation, and calcination is used.
Patent Information
- Application Number
- CN202411262975.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-10
AI Technical Summary
The recycling of lithium-ion battery positive electrode materials is inefficient, and the mixed salt solution cannot be directly used for sodium-ion batteries due to the lack of metal elements, while O3 type sodium ion battery materials face issues with phase transitions and stability, limiting their capacity and cycle stability.
A regenerated O3-type high-entropy layered sodium-ion battery cathode material is developed, utilizing a mixed salt solution from lithium battery recycling, with a chemical formula Na1-aLi a Ni x Fe y Mn z Co m Al n Cu 1-x-y-z-m-n O2, where Na and Li are in the alkali metal layer and Ni, Fe, Mn, Co, Al, and Cu are in the transition metal layer, arranged disorderly, and a specific preparation method involving sulfate leaching, precipitation, and calcination is used.
The solution enables efficient utilization of waste lithium battery materials, improves electrochemical performance by inhibiting irreversible phase transitions, and enhances thermal stability, facilitating the recycling of waste lithium batteries into high-performance sodium-ion batteries.
Smart Images

Figure CN118782785B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion battery materials, and in particular relates to a regenerated O3 type high entropy layered sodium ion battery positive electrode material and a preparation method thereof. Background Art
[0002] With the rapid development of the new energy electric vehicle market, the treatment of retired lithium-ion batteries has gradually become a focus of attention. If improperly disposed of, it will cause great harm to the environment and also cause a waste of important precious metal resources. At present, the recycled black powder of lithium battery positive electrode materials includes LiCoO2, LiNi b Co c Mn 1-b-c O2、LiNi 0.8 Co 0.15 Al 0.05 O2, LiMn2O4, LiFePO4 materials, etc., as well as a small amount of Al, Cu and other current collector components. In industry, the H2SO4+H2O2 leaching method is usually used to recover the above-mentioned lithium battery positive electrode black powder. This process brings difficulties to the subsequent separation of metal elements. Therefore, the direct and efficient utilization of the recovered mixed salt solution is an effective way to solve the above problems. However, there are fewer metal elements involved in the positive electrode materials of lithium-ion batteries, and the above-mentioned mixed salt solution cannot be directly used. However, the positive electrode materials of sodium-ion batteries contain a variety of metal elements, so the above-mentioned mixed salt solution can be reused as the raw material of the positive electrode materials of sodium-ion batteries.
[0003] In addition, O3 type sodium ion battery positive electrode material Na x TMO2 has attracted the most attention due to its advantages of high theoretical specific capacity, low cost and easy preparation, but it has multiple phase transitions, Na + These defects limit the Na x The gram capacity and long cycle stability of TMO2 cathode materials. In recent years, the introduction of high entropy oxides has provided a possible solution to the above problems, stabilizing the main matrix through the entropy effect, thereby improving the electrochemical performance and thermal stability.
[0004] Therefore, there is an urgent need to provide a regenerated O3 type high entropy layered sodium ion battery positive electrode material and a preparation method thereof, which utilizes the mixed salt solution in lithium battery recycling containing metal elements such as Li, Ni, Co, Mn, Fe, Al and Cu as the main raw material for preparing high entropy sodium ion battery positive electrode material to achieve the recycling of waste lithium batteries, and at the same time, can also improve the electrochemical properties and thermal stability of sodium ions. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a regenerated O3-type high-entropy layered sodium-ion battery cathode material and a preparation method thereof.
[0006] To solve the above problems, the technical solution adopted by the present invention is as follows:
[0007] In the first aspect, a regenerated O3-type high-entropy layered sodium-ion battery cathode material is provided. The chemical formula of the material is Na 1-a Li a Ni x Fe y Mn z Co m Al n Cu 1-x-y-z-m-n O2 (0 < a ≤ 0.1, 0 < x, y, z < 1, 0 < m, n < 0.5), belonging to the hexagonal crystal system, and the space group is R-3m;
[0008] Among them, Na and Li elements are in the same alkali metal layer and are arranged disorderly; Ni, Fe, Mn, Co, Al and Cu elements are in the same transition metal layer and are arranged disorderly; the arrangement mode of the transition metal layer is ABCABC.
[0009] As an implementation mode of the invention, a is 0.01 - 0.1, x is 0.30 - 0.65, y is 0.20 - 0.50, z is 0.05 - 0.35, m is 0.05 - 0.40, and n is 0.01 - 0.10.
[0010] As an implementation mode of the invention, a is 0.01 - 0.06, x is 0.35 - 0.50, y is 0.25 - 0.40, z is 0.10 - 0.20, m is 0.10 - 0.25, and n is 0.03 - 0.08.
[0011] In the second aspect, a preparation method of a regenerated O3-type high-entropy layered sodium-ion battery cathode material as described in the first aspect is provided, including the following steps:
[0012] (1) Treat the waste lithium-ion battery cathode material to obtain a sulfate mixed solution; the waste lithium-ion battery cathode material includes LiFePO4, LiNi b Co c Mn 1-b-c O2, Al, Cu, and one or more of LiCoO2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiMn2O4;
[0013] (2) Determine the concentration of each metal ion in the sulfate mixed solution by ICP, and add an appropriate amount of salt reagent to make the concentration of all metal ions in the solution meet the stoichiometric ratio;
[0014] (3) adding a Na2CO3 solution to the sulfate mixed solution after adjusting the ion concentration to obtain a precipitate, filtering and drying the precipitate to obtain a precursor;
[0015] (4) The obtained precursor is evenly mixed with a certain amount of sodium carbonate or sodium oxide, and calcined at 700-1000 °C for 10-20 h; thereafter, the temperature is reduced to 500-600 °C at a rate of 3-10 °C / min and then naturally reduced to room temperature to obtain the regenerated O3-type high entropy layered sodium ion battery positive electrode material.
[0016] As an embodiment of the invention, in step (1), after calcining the waste lithium-ion battery positive electrode material at 650-950°C for 1-5 h, the calcined product is mixed with H2SO4 and H2O2 in a mass ratio of 1:(1-4) and poured into a reaction kettle, and the reaction temperature is set to 40-80°C and the reaction time is 5-15 h to obtain the sulfate mixed solution; wherein the concentration of the H2SO4 solution is 50%-80%, and the concentration of the H2O2 solution is 20%-50%;
[0017] The solid-liquid ratio of the calcined product to the H2SO4 solution is 10-100 g / L.
[0018] As an embodiment of the invention, in step (1), a mixed solution of waste lithium-ion battery positive electrode materials, H2SO4 and H2O2 in a mass ratio of 1:(1-4) is poured into a reactor, the reaction temperature is set to 40-80°C, the reaction time is 10-20 h, and the sulfate mixed solution is obtained after filtering; wherein the concentration of the H2SO4 solution is 50%-80%, and the concentration of the H2O2 solution is 20%-50%;
[0019] Among them, the solid-liquid ratio of waste lithium-ion battery positive electrode materials and H2SO4 solution is 10~100 g / L.
[0020] As an embodiment of the invention, the salt reagent in step (2) is sulfate, nitrate or hydrochloride of Li, Ni, Co, Mn, Fe, Al and Cu elements.
[0021] As an embodiment of the invention, in step (3), the concentration of the added Na2CO3 solution is 10% to 20%, and the mass ratio of the added Na2CO3 solution to the sulfate mixed solution is (1 to 1.5):1;
[0022] In step (4), the molar ratio of sodium carbonate or sodium oxide to the precursor is (0.90-1.15):1.
[0023] As an embodiment of the invention, in step (4), the calcination temperature is 800-900°C, the calcination time is 15-20h, the calcination atmosphere is air or oxygen, and the programmed cooling rate is 5-10°C / min.
[0024] In a third aspect, a sodium ion battery is provided, the sodium ion battery comprising a positive electrode sheet and a negative electrode sheet, the positive electrode sheet comprising 80% of a positive electrode material, 10% of conductive carbon black, and 10% of polyvinylidene fluoride;
[0025] Wherein, the positive electrode material is the regenerated O3 type high entropy layered sodium ion battery positive electrode material described in the first aspect, or is obtained by the preparation method described in the second aspect.
[0026] The beneficial effects of adopting the above technical solution are:
[0027] The regenerated O3 type high entropy layered sodium ion battery positive electrode material and the preparation method thereof provided by the present invention realize the efficient utilization of waste lithium battery positive electrode materials, and at the same time adopt the element composition control strategy to synthesize the high entropy sodium ion battery positive electrode material with the waste lithium battery positive electrode material leachate as raw material. The positive electrode material obtained by the present invention can effectively inhibit Na + Irreversible phase transition during intercalation, thus enhancing its kinetics and improving electrochemical performance;
[0028] In addition, since the raw materials used come from the leachate of the positive electrode materials of waste lithium batteries, the recycling of waste lithium batteries can be achieved, which is environmentally friendly, economical and energy-saving. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the XRD result diagram of the regenerated O3 type high entropy layered sodium ion battery positive electrode material prepared in Example 1 of the present invention.
[0030] Figure 2 This is the XRD result diagram of the regenerated O3 type high entropy layered sodium ion battery positive electrode material prepared in Example 2 of the present invention.
[0031] Figure 3 This is the XRD result diagram of the regenerated O3 type high entropy layered sodium ion battery positive electrode material prepared in Example 3 of the present invention.
[0032] Figure 4 It is a charge and discharge curve diagram of the sodium ion button battery prepared in Example 2 of the present invention.
[0033] Figure 5 It is a charge and discharge curve diagram of the sodium ion button battery prepared in Example 4 of the present invention.
[0034] Figure 6 It is a cycle curve diagram of the sodium ion soft-pack battery prepared in Example 2 of the present invention and Comparative Example 2.
[0035] Figure 7 It is a cycle curve diagram of the sodium ion button batteries prepared in Examples 1-4 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION
[0036] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention is clearly and completely described below in conjunction with specific embodiments.
[0037] Example 1
[0038] A regenerative O3 type high entropy layered sodium ion battery cathode material and investigation of its sodium ion battery performance.
[0039] 1. Preparation of regenerated O3 type high entropy layered sodium ion battery cathode material
[0040] The chemical formula of the positive electrode material is Na 0.98 Li 0.02 Ni 0.38 Fe 0.30 Mn 0.12 Co 0.10 Al 0.05 Cu 0.05 O2, the preparation method thereof comprises the following steps:
[0041] (1) Processing waste lithium-ion battery positive electrode materials to obtain a sulfate mixed solution; as shown in Table 1, the waste lithium-ion battery positive electrode materials include LiFePO4, LiNi 0.8 Co 0.1 Mn 0.1 O2, Al, Cu, as well as LiCoO2 and LiMn2O4.
[0042] Table 1
[0043]
[0044] The processing steps include:
[0045] After calcining the waste lithium-ion battery positive electrode material at 650°C for 5 h, the calcined product was mixed with H2SO4 and H2O2 in a mass ratio of 1:1 and poured into a reactor, the reaction temperature was set to 40°C, and the reaction time was set to 15 h to obtain the sulfate mixed solution; wherein the concentration of the H2SO4 solution was 50%, and the concentration of the H2O2 solution was 20%;
[0046] Among them, the solid-to-liquid ratio of the calcined product and H2SO4 is 10 g / L.
[0047] (2) Determine the concentration of each metal ion in the sulfate mixed solution by ICP, and add an appropriate amount of salt reagent to make the concentration of all metal ions in the solution meet the stoichiometric ratio;
[0048] In this embodiment, the concentration of each metal ion in the sulfate mixed solution was determined by ICP as follows: Li is 630 mg / L, Ni is 2230 mg / L, Co is 589 mg / L, Mn is 650 mg / L, Fe is 1574 mg / L, Al is 55 mg / L, and Cu is 217 mg / L. The added salt reagents are: ferrous sulfate, aluminum sulfate and cupric sulfate, and the adjusted metal ion concentration ratio is Li:Ni:Co:Mn:Fe:Al:Cu=6.3:22.3:5.9:6.5:16.7:1.4:3.2.
[0049] (3) adding a 10% Na2CO3 solution to the sulfate mixed solution after adjusting the ion concentration to obtain a precipitate, filtering and drying the precipitate to obtain a precursor; the mass ratio of the added Na2CO3 solution to the sulfate mixed solution is 1:1;
[0050] (4) Sodium carbonate and the precursor were mixed evenly at a molar ratio of 0.90:1, and calcined at 800 °C for 20 h; then, the temperature was cooled to 600 °C at a rate of 5 °C / min and then naturally cooled to room temperature to obtain the regenerated O3 type high entropy layered sodium ion battery positive electrode material. The XRD pattern of the obtained material is shown in Figure 1 The results show that the obtained material is Na 0.98 Li 0.02 Ni 0.3 8Fe 0.30 Mn 0.12 Co 0.10 Al 0.05 Cu 0.05 O2, which belongs to the hexagonal crystal system.
[0051] 2. Preparation of Na 0.98 Li 0.02 Ni 0.38 Fe 0.30 Mn 0.12 Co 0.10 Al 0.05 Cu 0.05 O2 material electrode
[0052] The composition of the positive electrode of the sodium ion battery (based on the mass fraction of the positive electrode material as 100%): 80% Na 0.98 Li 0.02 Ni 0.38 Fe 0.30 Mn 0.12 Co0.10 Al 0.05 Cu 0.05 O2, 10% conductive carbon black, and 10% polyvinylidene fluoride. The counter electrode of the sodium ion half-cell is a metal sodium sheet, and the counter electrode of the sodium ion soft pack battery is pre-sodiumized hard carbon. The solvent of the electrolyte is propylene carbonate. The electrolyte salt is sodium hexafluorophosphate, and the molar concentration in the electrolyte is 1.0 mol / L.
[0053] 3. Assemble the battery
[0054] The electrode sheets, sodium sheets, electrolyte and other necessary battery components, such as a diaphragm and a housing, made of the above-prepared materials were assembled into a CR2032 type button battery in a glove box filled with argon.
[0055] Example 2
[0056] A regenerative O3 type high entropy layered sodium ion battery cathode material and investigation of its sodium ion battery performance.
[0057] 1. Preparation of regenerated O3 type high entropy layered sodium ion battery cathode material
[0058] The chemical formula of the positive electrode material is Na 0.95 Li 0.05 Ni 0.45 Fe 0.25 Mn 0.10 Co 0.10 Al 0.07 Cu 0.03 O2, the preparation method thereof comprises the following steps:
[0059] (1) Processing waste lithium-ion battery positive electrode materials to obtain a sulfate mixed solution; as shown in Table 2, the waste lithium-ion battery positive electrode materials include LiFePO4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, Al, Cu, and LiNi 0.8 Co 0.15 Al 0.05 O2 and LiMn2O4.
[0060] Table 2
[0061]
[0062] The processing steps include:
[0063] After calcining the waste lithium-ion battery positive electrode material at 850°C for 3 h, the calcined product was mixed with H2SO4 and H2O2 in a mass ratio of 1:2 and poured into a reactor, the reaction temperature was set to 65°C, and the reaction time was 10 h to obtain the sulfate mixed solution; wherein the concentration of the H2SO4 solution was 60%, and the concentration of the H2O2 solution was 30%;
[0064] The solid-to-liquid ratio of the calcined product to the H2SO4 solution is 60 g / L.
[0065] (2) Determine the concentration of each metal ion in the sulfate mixed solution by ICP, and add an appropriate amount of salt reagent to make the concentration of all metal ions in the solution meet the stoichiometric ratio;
[0066] In this embodiment, the concentration of each metal ion in the sulfate mixed solution was determined by ICP as follows: Li is 615 mg / L, Ni is 2640 mg / L, Co is 570 mg / L, Mn is 520 mg / L, Fe is 1200 mg / L, Al is 189 mg / L, and Cu is 192 mg / L. The added salt reagents are: cobalt sulfate, manganese sulfate and ferrous sulfate, and the adjusted metal ion concentration ratio is Li:Ni:Co:Mn:Fe:Al:Cu=6.15:26.4:5.9:5.5:14:1.9:1.92.
[0067] (3) adding a 15% Na2CO3 solution to the sulfate mixed solution after adjusting the ion concentration to obtain a precipitate, filtering and drying the precipitate to obtain a precursor; the mass ratio of the added Na2CO3 solution to the sulfate mixed solution is 1.3:1;
[0068] (4) Sodium carbonate and the precursor were mixed evenly in a molar ratio of 1:1, and calcined at 850 °C for 17 h; then, the temperature was cooled to 590 °C at a rate of 7 °C / min and then naturally cooled to room temperature to obtain the regenerated O3 type high entropy layered sodium ion battery positive electrode material. The XRD pattern of the obtained material is as follows: Figure 2 The results show that the obtained material is Na 0.95 Li 0.05 Ni 0.45 Fe 0.25 Mn 0.10 Co 0.10 Al 0.07 Cu 0.03 O2, which belongs to the hexagonal crystal system.
[0069] 2. Preparation of Na 0.95 Li 0.05 Ni 0.45 Fe 0.25 Mn0.10 Co 0.10 Al 0.07 Cu 0.03 O2 material electrode
[0070] The composition of the positive electrode of the sodium ion battery (based on the mass fraction of the positive electrode material as 100%): 80% Na 0.95 Li 0.05 Ni 0.45 Fe 0.25 Mn 0.10 Co 0.10 Al 0.07 Cu 0.03 O2, 10% conductive carbon black, and 10% polyvinylidene fluoride. The counter electrode of the sodium ion half-cell is a metal sodium sheet, and the counter electrode of the sodium ion soft pack battery is pre-sodiumized hard carbon. The solvent of the electrolyte is propylene carbonate. The electrolyte salt is sodium hexafluorophosphate, and the molar concentration in the electrolyte is 1.0 mol / L.
[0071] 3. Assemble the battery
[0072] The prepared positive electrode material, sodium sheet, electrolyte and other necessary battery components, such as diaphragm and shell, are assembled into a CR2032 button battery in a glove box filled with argon. At the same time, the prepared positive electrode material, hard carbon, electrolyte and other necessary battery components, such as aluminum-plastic film and tabs, are assembled into a square soft-pack battery.
[0073] Example 3
[0074] A regenerative O3 type high entropy layered sodium ion battery cathode material and investigation of its sodium ion battery performance.
[0075] 1. Preparation of regenerated O3 type high entropy layered sodium ion battery cathode material
[0076] The chemical formula of the positive electrode material is Na 0.94 Li 0.06 Ni 0.35 Fe 0.25 Mn 0.15 Co 0.20 Al 0.03 Cu 0.02 O2, the preparation method thereof comprises the following steps:
[0077] (1) Processing waste lithium-ion battery positive electrode materials to obtain a sulfate mixed solution; as shown in Table 3, the waste lithium-ion battery positive electrode materials include LiFePO4, LiNi 0.5 Co 0.2 Mn 0.3 O2, Al, Cu, and LiCoO2.
[0078] Table 3
[0079]
[0080] The processing steps include:
[0081] After calcining the waste lithium-ion battery positive electrode material at 950°C for 1 h, the calcined product was mixed with H2SO4 and H2O2 in a mass ratio of 1:4 and poured into a reactor, the reaction temperature was set to 80°C, and the reaction time was 5 h to obtain the sulfate mixed solution; wherein the concentration of the H2SO4 solution was 80%, and the concentration of the H2O2 solution was 50%;
[0082] The solid-liquid ratio of the calcined product to the H2SO4 solution is 100 g / L.
[0083] (2) Determine the concentration of each metal ion in the sulfate mixed solution by ICP, and add an appropriate amount of salt reagent to make the concentration of all metal ions in the solution meet the stoichiometric ratio;
[0084] In this embodiment, the concentration of each metal ion in the sulfate mixed solution was determined by ICP as follows: Li was 750 mg / L, Ni was 2050 mg / L, Co was 1180 mg / L, Mn was 380 mg / L, Fe was 1400 mg / L, Al was 80 mg / L, and Cu was 128 mg / L. The added salt reagent was manganese sulfate, and the adjusted metal ion concentration ratio was Li:Ni:Co:Mn:Fe:Al:Cu=7.5:20.5:11.8:8.25:14:0.8:1.28.
[0085] (3) adding a 20% Na2CO3 solution to the sulfate mixed solution after adjusting the ion concentration to obtain a precipitate, filtering and drying the precipitate to obtain a precursor; the mass ratio of the added Na2CO3 solution to the sulfate mixed solution is 1.5:1;
[0086] (4) Sodium oxide and the precursor were mixed evenly in a molar ratio of 1.15:1, and calcined at 900 °C for 15 h; then, the temperature was cooled to 560 °C at a rate of 10 °C / min and then naturally cooled to room temperature to obtain the regenerated O3 type high entropy layered sodium ion battery positive electrode material. The XRD pattern of the obtained material is as follows: Figure 3 The results show that the obtained material is Na 0.94 Li 0.06 Ni 0.3 5Fe 0.25 Mn 0.15 Co 0.20 Al 0.03 Cu 0.02O2, which belongs to the hexagonal crystal system.
[0087] 2. Preparation of Na 0.94 Li 0.06 Ni 0.35 Fe 0.25 Mn 0.15 Co 0.20 Al 0.03 Cu 0.02 O2 material electrode
[0088] The composition of the positive electrode of the sodium ion battery (based on the mass fraction of the positive electrode material as 100%): 80% Na 0.94 Li 0.06 Ni 0.35 Fe 0.25 Mn 0.15 Co 0.20 Al 0.03 Cu 0.02 O2, 10% conductive carbon black, and 10% polyvinylidene fluoride. The counter electrode of the sodium ion half-cell is a metal sodium sheet, and the counter electrode of the sodium ion soft pack battery is pre-sodiumized hard carbon. The solvent of the electrolyte is propylene carbonate. The electrolyte salt is sodium hexafluorophosphate, and the molar concentration in the electrolyte is 1.0 mol / L.
[0089] 3. Assemble the battery
[0090] The prepared positive electrode material, sodium sheet, electrolyte and other necessary battery components, such as a diaphragm and a housing, were assembled into a CR2032 button battery in a glove box filled with argon.
[0091] Example 4
[0092] A regenerative O3 type high entropy layered sodium ion battery cathode material and its sodium ion battery performance, the chemical formula of the cathode material is Na 0.95 Li 0.05 Ni 0.45 Fe 0.25 Mn 0.10 Co 0.10 Al 0.07 Cu 0.03 O2.
[0093] The preparation method is the same as that of Example 2, except that: in step (1), the waste lithium-ion battery positive electrode material is treated by the following steps to obtain a sulfate mixed solution;
[0094] A mixed solution of waste lithium-ion battery positive electrode materials, H2SO4 and H2O2 in a mass ratio of 1:2 is poured into a reactor, the reaction temperature is set to 65°C, the reaction time is 10 h, and the solid-liquid mixture after the reaction is filtered under negative pressure to obtain the sulfate mixed solution; wherein the concentration of the H2SO4 solution is 60%, and the concentration of the H2O2 solution is 30%; wherein the solid-liquid ratio of the calcined product and the H2SO4 solution is 60 g / L.
[0095] The prepared positive electrode material, sodium sheet, electrolyte and other necessary battery components, such as a diaphragm and a housing, were assembled into a CR2032 button battery in a glove box filled with argon.
[0096] Comparative Example 1
[0097] In this comparative example, a positive electrode material is synthesized and its sodium ion battery performance is investigated. The preparation method of the positive electrode material is consistent with that of Example 2, except that in step (4), the precursor is not mixed evenly with sodium carbonate, but is directly calcined at 850°C.
[0098] The prepared positive electrode material, sodium sheet, electrolyte and other necessary battery components, such as a diaphragm and a housing, were assembled into a CR2032 button battery in a glove box filled with argon.
[0099] Comparative Example 2
[0100] In this comparative example, a positive electrode material is synthesized and its sodium ion battery performance is investigated. The preparation method of the positive electrode material is the same as that of Example 2, except that after the calcination in step (4) is completed, it is directly cooled naturally to room temperature.
[0101] The prepared positive electrode material, sodium sheet, electrolyte and other necessary battery components, such as diaphragm and shell, are assembled into a CR2032 button battery in a glove box filled with argon. At the same time, the prepared positive electrode material, hard carbon, electrolyte and other necessary battery components, such as aluminum-plastic film and tabs, are assembled into a square soft-pack battery.
[0102] Comparative Example 3
[0103] In this comparative example, a positive electrode material is synthesized and its sodium ion battery performance is investigated. The preparation method of the positive electrode material is the same as that of Example 2, except that: in step (3), the sulfate mixed solution after adjusting the ion concentration is dried to obtain a powder; in step (4), sodium carbonate is evenly mixed with the powder and then calcined.
[0104] The prepared positive electrode material, sodium sheet, electrolyte and other necessary battery components, such as a diaphragm and a housing, were assembled into a CR2032 button battery in a glove box filled with argon.
[0105] Effect example:
[0106] The sodium ion button batteries prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were subjected to charge and discharge capacity tests, rate performance tests, cycle performance tests, and thermal stability tests. The charge and discharge curves of the sodium ion button batteries prepared in Examples 2 and 4 are shown in Figures 1 to 3. Figure 4 and Figure 5 As shown; the sodium ion soft pack battery cycle curves prepared in Example 2 and Comparative Example 2 are shown in Figure 6 As shown, the cycle performance test results of Example 1-Example 4 and Comparative Example 1-Comparative Example 3 are as follows Figure 7 The final performance test results are shown in Table 4.
[0107] Table 4
[0108]
[0109] From Table 4 and Figure 7 It can be seen that Examples 1 to 4 have excellent rate performance and cycle performance, showing excellent electrochemical performance.
[0110] In Comparative Example 1, the precursor is not evenly mixed with sodium carbonate and is directly calcined at 850°C. The synthesized oxide material lacks the sodium ions stored in the alkali metal layer and does not have the ability to remove and embed sodium ions. Therefore, its rate performance and cycle performance are poor during the charge and discharge process, and the assembled button battery does not have the ability to store charge.
[0111] In Comparative Example 2, after calcination, the material was directly cooled naturally to room temperature. Since the cooling rate during the natural cooling process was relatively fast, the material did not form a complete layered crystal structure. Therefore, its rate performance and cycle performance were relatively poor, and its ability to store charge was relatively weak.
[0112] In Comparative Example 3, after adjusting the ion concentration, the sulfate mixed solution is dried to obtain a powder, and then sodium carbonate is mixed with the powder evenly and then calcined. Since a transition metal carbonate precursor with a stable crystal structure is not formed before calcination, and it is difficult for sulfate to react with sodium carbonate to form a stable layered crystal structure during the calcination process, its rate performance and cycle performance are poor.
Claims
1. A regenerated O3 type high entropy layered sodium ion battery positive electrode material, characterized in that: The chemical formula of the said material is Na 1-a Li a Ni x Fe y Mn z Co m Al n Cu 1-x-y-z-m-n O2, 0 < a ≤ 0.1, 0 < x, y, z < 1, 0 < m, n < 0.5, belonging to the hexagonal crystal system, with the space group of R-3m; Among them, Na and Li elements are in the alkali metal layer and are arranged in a disordered manner; Ni, Fe, Mn, Co, Al and Cu elements are in the transition metal layer and are arranged in a disordered manner; the arrangement of the transition metal layer is ABCABC; The method for preparing a regenerated O3 type high entropy layered sodium ion battery positive electrode material comprises the following steps: (1) treating the positive electrode material of waste lithium-ion batteries to obtain a sulfate mixed solution; the positive electrode material of the waste lithium-ion batteries comprises LiFePO4, LiNi b Co c Mn 1-b-c O2, Al, Cu, LiCoO2, LiNi 0.8 Co 0.15 Al 0.05 One or more of O2, LiMn2O4; (2) Determine the concentration of each metal ion in the sulfate mixed solution by ICP, and add an appropriate amount of salt reagent to make the concentration of all metal ions in the solution meet the stoichiometric ratio; (3) adding a Na2CO3 solution to the sulfate mixed solution after adjusting the ion concentration to obtain a precipitate, filtering and drying the precipitate to obtain a precursor; (4) The obtained precursor is mixed evenly with sodium carbonate or sodium oxide, and calcined at 700-1000 °C for 10-20 h; thereafter, the temperature is reduced to 500-600 °C at a rate of 3-10 °C / min and then naturally reduced to room temperature to obtain the regenerated O3 type high entropy layered sodium ion battery positive electrode material, and the molar ratio of sodium carbonate or sodium oxide to the precursor is (0.90-1.15):
1.
2. A regenerated O3 type high entropy layered sodium ion battery positive electrode material according to claim 1, characterized in that: a is 0.01~0.1, x is 0.30~0.65, y is 0.20~0.50, z is 0.05~0.35, m is 0.05~0.40, and n is 0.01~0.
10.
3. A regenerated O3 type high entropy layered sodium ion battery positive electrode material according to claim 2, characterized in that: a is 0.01~0.06, x is 0.35~0.50, y is 0.25~0.40, z is 0.10~0.20, m is 0.10~0.25, and n is 0.03~0.
08.
4. A regenerated O3 type high entropy layered sodium ion battery positive electrode material according to claim 1, characterized in that: In step (1), the waste lithium-ion battery positive electrode material is calcined at 650-950°C for 1-5 h, and the calcined product is mixed with H2SO4 and H2O2 in a mass ratio of 1:(1-4) and poured into a reaction kettle, and the reaction temperature is set to 40-80°C and the reaction time is 5-15 h to obtain the sulfate mixed solution; wherein the concentration of the H2SO4 solution is 50%-80%, and the concentration of the H2O2 solution is 20%-50%; The solid-liquid ratio of the calcined product to the H2SO4 solution is 10-100 g / L.
5. The regenerated O3 type high entropy layered sodium ion battery positive electrode material according to claim 1, characterized in that: In step (1), a mixed solution of waste lithium-ion battery positive electrode materials, H2SO4 and H2O2 in a mass ratio of 1:(1-4) is poured into a reactor, the reaction temperature is set to 40-80°C, the reaction time is 10-20 h, and the sulfate mixed solution is obtained after filtering; wherein the concentration of the H2SO4 solution is 50%-80%, and the concentration of the H2O2 solution is 20%-50%; Among them, the solid-liquid ratio of waste lithium-ion battery positive electrode materials and H2SO4 solution is 10~100 g / L.
6. A regenerated O3 type high entropy layered sodium ion battery positive electrode material according to claim 1, characterized in that: The salt reagent in step (2) is sulfate, nitrate or hydrochloride of Li, Ni, Co, Mn, Fe, Al and Cu elements.
7. The regenerated O3 type high entropy layered sodium ion battery positive electrode material according to claim 1, characterized in that: In step (3), the concentration of the added Na2CO3 solution is 10%~20%, and the mass ratio of the added Na2CO3 solution to the sulfate mixed solution is (1~1.5):
1.
8. The regenerated O3 type high entropy layered sodium ion battery positive electrode material according to claim 1, characterized in that: In step (4), the calcination temperature is 800-900 °C, the calcination time is 15-20 h, the calcination atmosphere is air or oxygen, and the cooling rate is 5-10 °C / min.
9. A sodium ion battery, characterized in that: The sodium ion battery comprises a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet comprises 80% of a positive electrode material, 10% of conductive carbon black, and 10% of polyvinylidene fluoride; Wherein, the positive electrode material is the regenerated O3 type high entropy layered sodium ion battery positive electrode material as described in any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preparing sodium-ion battery positive electrode material by recycling waste battery positive electrode (nickel cobalt lithium manganate) and application of sodium-ion battery positive electrode material
CN115611321A
Method for recycling positive electrode material from waste sodium-ion battery
CN116073011A
High-entropy sodium ion battery positive electrode material
CN116799218A
O3-type high-entropy layered manganese-based sodium-ion battery positive electrode material and preparation method and application thereof
CN117088416A
Lithiated oxide materials and methods of manufacture
US20030022063A1
